2009
DOI: 10.1111/j.1749-6632.2009.04814.x
|View full text |Cite|
|
Sign up to set email alerts
|

Infections May Have a Protective Role in the Etiopathogenesis of Celiac Disease

Abstract: Infectious agents have been implicated in the pathogenesis of many autoimmune diseases via various pathogenic mechanisms, such as molecular mimicry, resulting in modulation of the host's immune tolerance. In the following article we examine the association between serological evidence of past infection with Toxoplasma gondii, rubella virus, cytomegalovirus, Treponema pallidum, and Epstein-Barr virus, and the co-existence of celiac disease. Our results imply that certain infections may generate an immunological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 32 publications
2
27
1
1
Order By: Relevance
“…9 It has been proposed that some immunologically relevant CD-associated alleles-including the SH2B3 rs3184504*A allele, which plays a protective role against bacterial infection-may have undergone positive selection rather recently. 8 This finding, along with those in other recent studies of the role of infections 10 and intestinal indigenous microflora composition 11,12 in CD, show that immune reactions to gluten are strongly influenced by changes in the intestinal microbiome.…”
supporting
confidence: 72%
“…9 It has been proposed that some immunologically relevant CD-associated alleles-including the SH2B3 rs3184504*A allele, which plays a protective role against bacterial infection-may have undergone positive selection rather recently. 8 This finding, along with those in other recent studies of the role of infections 10 and intestinal indigenous microflora composition 11,12 in CD, show that immune reactions to gluten are strongly influenced by changes in the intestinal microbiome.…”
supporting
confidence: 72%
“…In line with this, we found that EBV and HSV-1 added both to the explanation of ethnic differences in CDA. Previously, we observed inverse associations between combined CMV, EBV and/or HSV-1 infections and TG2A positivity, which may indicate a cumulative effect of herpesviruses, irrespective of type of viral infection 47. CMV-infected children were more often infected with other herpesviruses.…”
Section: Discussionmentioning
confidence: 64%
“…Also, early life infections [46] and gastrointestinal infections such as rotavirus infections [47] have been suggested to serve as additional triggers for celiac disease development. In contrast, there is a possibility that clinical or subclinical infections by Epstein-Barr virus, cytomegalovirus, and rubella might have a protective effect on the emergence of celiac disease [48], a conception well in keeping with the finding that the prevalence of celiac disease is lower in areas with inferior prosperity and standard hygiene [49].…”
Section: Environmental and Genetic Factors Facilitating Celiac Diseasementioning
confidence: 92%